2012
DOI: 10.1007/s10930-012-9441-6
|View full text |Cite
|
Sign up to set email alerts
|

An Arsenic Fluorescent Compound as a Novel Probe to Study Arsenic-Binding Proteins

Abstract: Arsenic-binding proteins are under continuous research. Their identification and the elucidation of arsenic/protein interaction mechanisms are important because the biological effects of these complexes may be related not only to arsenic but also to the arsenic/protein structure. Although many proteins bearing a CXXC motif have been found to bind arsenic in vivo, new tools are necessary to identify new arsenic targets and allow research on protein/arsenic complexes. In this work, we analyzed the performance of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 55 publications
0
4
0
Order By: Relevance
“…It has been demonstrated that binding to PAO does not induce alterations in the structure of Trx. 103…”
Section: Thioredoxin Fusion Proteinsmentioning
confidence: 99%
“…It has been demonstrated that binding to PAO does not induce alterations in the structure of Trx. 103…”
Section: Thioredoxin Fusion Proteinsmentioning
confidence: 99%
“…Besides these EDT-containing molecules, a similar As(III)-based probe, APAO-FITC, was synthesized with only one As-based moiety with the EDT being replaced by two hydroxyl groups (-OH). APAO-FITC has been shown to label native As-binding proteins without strong disturbance on their secondary structures (Femia et al, 2012). To expand the toolbox of As(III)-based probes, the biotin-avidin system was then taken into consideration while the As(III)-binding proteins could be analyzed by the combination of proteome microarray assay with biotin-conjugated As, i.e., Biotin-As.…”
Section: The Thiol-reactive Fluorescent Probesmentioning
confidence: 99%
“…The first generation of As(III)-based fluorescent probes, FLAsH-EDT 2 and ReAsH-EDT 2 , mainly target proteins with genetically fused tetracysteine tag since this motif seems to be rare among native proteins (Femia et al, 2012). Moreover, two As-based moieties of the probes result in stable protein labeling, and these two probes work successfully in the visualization of intracellular proteins as well as in affinity chromatography to track arsenic-binding proteins (Griffin et al, 1998).…”
Section: The Thiol-reactive Fluorescent Probesmentioning
confidence: 99%
“…7,22 By continuously elucidating the structures of arsenic-binding proteins, it is possible to understand how arsenic affects cells. 31 Various data from biomolecular studies show that arsenic binding to macromolecules causes heavy metal sequestration in bacterial proteins. However, the precise mechanism of arsenic transfer into human cells is currently unknown.…”
Section: Introductionmentioning
confidence: 99%